Prediction model of cutting force by cutting parameters using response surface methodology in end milling of steel AISI 1020 - Patwari, Muhammed Anayet Ullah; Amin, A. K. M. Nurul; Faris, Waleed Fekry; Alam, S. (2008)
This paper describes mathematically the cutting force prediction model based on different cutting parameters in end milling of steel AISI1020. In this study, Cutting tests were conducted mainly on Vertical Machining Center for end milling of steel using coated TiN insert under dry conditions and full immersion cutting. The mathematical model for the cutting force has been developed, in terms of cutting parameters like cutting speed, feed rate, and axial depth of cut using design of experiments and the response surface methodology (RSM). All the individual cutting parameters affect on cutting forces as well as their interaction were also investigated in this study. The second order quadratic equation shows, based on the variance analysis, that the most influential input parameter was the feed rate followed by axial depth of cut and, finally, by the cutting speed. The CCD model developed by RSM using Design Expert package is able to provide accurately the predicted values of cutting force close to actual values found in the experiments.